Fake news, big data and risks for democracy: New challenges for the information and media competence - Ottonicar, Selma Leticia Capinzaiki [UNESP]; Valentim, Marta Lígia Pomim [UNESP]; Jorge, Leandro Feitosa; Mosconi, Elaine [UNESP] (My University, 2021)
Systematic review of the literature on fake news and their risks for democracy and how to approach it from the perspective of informational and media competence. A review protocol was carried out and, afterwards, scientific articles were searched in two databases, Web of Science and Scientific Electronic Library Online. The recovered articles were published in several scientific areas, demonstrating the multidisciplinary nature of this topic. In addition, there was an increase in publications in 2018, indicating the currency of this subject in the academic area. Most of the studies analyzed suggest applying information and media literacy in the curricula of schools and universities. However, little has been said about the possible solutions to avoid them in the political field. In this sense, there is a knowledge gap in relation to information and media competence in the political context; thus, it becomes an opportunity for future research.
Fake news, big data e o risco à democracia: Novos desafios à competência em informação e midiática
Keywords: Big data; Fake news; Information literacy; Media literacy; Systematic literature review